Desain dan Implementasi Program E-Learning Berbasiskan ICT - Afrizal Mayub; Rendy W Wardana (PendIPA Journal of Science Education, 2022)
This paper describes the Design and Implementation of ICT-based E-learning programs that can be used for learning either through computer networks or personal computers (PCs) with CD ROMs. This research includes software engineering with methods of analysis, design, coding and evaluation. Based on the results of the study, it was obtained that the Design and Implementation of E-learning Program consisted of modules of material presentation, demo, analysis, examination, Practice test, Problem Answer and Help Module. The module can function as a learning tool that facilitates learning needs for learning activities that include reading, staring, watching, peeping, observing, simulating, demonstrating, answering questions, entering data, listening, tracing teaching materials, working on problems, and finding answers to problems.